Unihemispheric Dual-site Anodal tDCS for Lower Limb Motor Function in Chronic Stroke Patients: A Randomized Clinical Trial - Somaye Azarnia; kamran Ezzati; Alia Saberi; Yaser Moaddabi; Babak Bakhshayesh Eghbali (Caspian Journal of Neurological Sciences)
Background: A cerebrovascular accident results in behavioral deficits as a result of damage to the brain’s systems. The motor system is one of the most commonly affected nervous systems. Lower limb motor function is important to a person’s functional independence. Therefore, restoring lower limb motor function can be an important goal in rehabilitating patients after stroke. Scientists have shown the effects of non-invasive brain stimulation, such as tDCS, in improving the performance of stroke patients. Recently, researchers have proposed that unihemispheric dual-site anodal transcranial direct current stimulation (UHCDS a-tDCS) targeting the primary motor cortex (M1) and dorsolateral prefrontal cortex (DLPFC) could improve the effectiveness of a-tDCS in stroke rehabilitation. Objectives: This study aimed to examine the effect of simultaneous stimulation of two points on the function of the lower limbs of stroke patients. Materials & Methods:  This was a double-blind, randomized clinical trial. The study included 18 patients who had experienced their first chronic stroke. Participants were assigned to either experimental group 1 or group 2, with both undergoing 5 consecutive sessions of a-tDCS. In experimental group 1, patients received active a-tDCS targeting both the M1 and DLPFC, while in experimental group 2, patients received a-tDCS to the M1 and sham stimulation to the DLPFC. Lower limb motor function was assessed using the Fugl-Meyer and time up-and-go test. Assessments were made before and after 5 sessions. Results: The results indicate that following 5 sessions of a-tDCSM1-DLPFC, mobility and functional strength are better than a-tDCSM1 (P=0.04 and P=0.07). Conclusion: Dual site stimulation a-tDCSM1-DLPFC can further improve balance in patients with chronic stroke.